Acute Marijuana Use and Cerebellar Infarction - J Gordon Millichap (Pediatric Neurology Briefs)
Three adolescent cases of ischemic stroke involving the posterior fossa circulation and cerebellum occurred within days after the illicit use of marijuana and presented over a span of 5 years at St Louis University School of Medicine, MO.